Zawartość miedzi, ołowiu i kadmu w glebach i roślinach uprawianych w pobliżu Huty Miedzi "Głogów" = Copper, lead and cadmium content in soils and plants cultivated in the vicinity of Copper Smelter "Głogów" - Rosada, Janusz; Przewocka, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of conducted studies was to perform the phyto- and ecotoxicological assessment of areas located in the immediate vicinity of the Copper Smelter GŁOGÓW. The study determined the content of copper, lead and cadmium in soils and their impact on cereal crops. At total 10 points were set, from which soils and plants samples were collected. Points were chosen based on three aspects: points location relative to emitters of pollutions, the level of soils pollution, also the representativeness of selected points to research areas.
Keywords: metale ciężkie; zanieczyszczenie gleb; zanieczyszczenia zbóż; heavy metals; soil pollution; cereal contamination